2022
DOI: 10.1155/2022/4342755
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of miR-372-3p Inhibits the Development of Diabetic Cardiomyopathy by Accelerating Angiogenesis via Activating the PI3K/AKT/mTOR/HIF-1α Signaling Pathway and Suppressing Oxidative Stress

Abstract: Background. DCM is the most common and malignant complication of diabetes. It is characterized by myocardial dilatation, hypertrophy, fibrosis, ventricular remodeling, and contractile dysfunction. Although many studies have demonstrated the function of miRNAs in the progression of DCM, but the specific role of miR-372-3p in DCM remains unknown. Methods. C57/BL6J mice were used to construct mouse models of DCM by intraperitoneal injection of STZ (50 mg/kg/d) for 5 consecutive days. Then the mice were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Our findings demonstrate for the first time that EPC-EXs miR-17-5p protect ECs and C2C12 cells from Hypoxia plus HG injury by targeting SPRED1 and activating the PI3K/Akt pathway, which is consistent with a previous study showing that the SPRED1-PI3K/Akt pathway is involved in regulating ECs and muscle cell functions [ 11 , 24 ]. A PI3K inhibitor (LY294002) has been used to address the participation of the PI3K/Akt pathway in regulating multiple cell functions [ 50 , 51 ]. Using a PI3K inhibitor, we further demonstrated that EPC-EXs enriched with miR-17-5p ameliorated HG plus hypoxia-induced EC (increasing viability, migration, and tube formation) and C2C12 cell (increasing viability and myotube size) dysfunction and apoptosis by activating the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate for the first time that EPC-EXs miR-17-5p protect ECs and C2C12 cells from Hypoxia plus HG injury by targeting SPRED1 and activating the PI3K/Akt pathway, which is consistent with a previous study showing that the SPRED1-PI3K/Akt pathway is involved in regulating ECs and muscle cell functions [ 11 , 24 ]. A PI3K inhibitor (LY294002) has been used to address the participation of the PI3K/Akt pathway in regulating multiple cell functions [ 50 , 51 ]. Using a PI3K inhibitor, we further demonstrated that EPC-EXs enriched with miR-17-5p ameliorated HG plus hypoxia-induced EC (increasing viability, migration, and tube formation) and C2C12 cell (increasing viability and myotube size) dysfunction and apoptosis by activating the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway and ECM-receptor interaction were significantly enriched in EC_1. PI3K-PKB/Akt is a highly conserved signaling pathway, and its activation mediates many cellular functions, including angiogenesis, survival, growth, transcription, proliferation, and apoptosis [31, 32]. ECMs interact with cell surface receptors to regulate cell behavior, such as cell communication, proliferation, migration, and adhesion [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway and ECM-receptor interaction were significantly enriched in EC_1. PI3K-PKB/Akt is a highly conserved signaling pathway, and its activation mediates many cellular functions, including angiogenesis, survival, growth, transcription, proliferation, and apoptosis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-327-3p was another EAT-derived miRNA increased in CAD patients [ 85 ], and it is involved in the development of diabetic cardiomyopathy (DCM). Recently, it was reported that the downregulation of miR-372-3p promotes angiogenesis while suppressing oxidative stress, presumably by targeting phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) in DCM mice [ 99 ]. That is to say that miR-372-3p can negatively regulate angiogenesis and increase oxidative stress.…”
Section: Micrornas Expressed In Human Eatmentioning
confidence: 99%
“… MicroRNA Underlying CVD [Ref.] Expression Change Reported Target, Effects Relevant to Cardiovascular System Reference miR-135b 1 CAD [ 85 ] Increased 2 HIP1, inhibited 3 EC proliferation, migration, and tube formation [ 92 ] 4 GPX4, promoted ferroptosis of 5 CM [ 95 ] miR-1231 CAD [ 85 ] Increased 6 CACNA2D2, aggravated arrhythmia [ 97 ] miR-372-3p CAD [ 85 ] Increased 7 PIK3CA, downregulation in 8 DCM mice promoted angiogenesis while suppressing oxidative stress [ 99 ] miR-6870-3p CAD [ 100 ] Increased 9 TOLLIP, increased the expression of inflammatory genes ( 10 TLR4, 11 IL-6, 12 JNK, 13 NF-κB, and 14 TNF-α) [ 100 ] miR-34a 15 SCD [ 91 ] …”
Section: Micrornas Expressed In Human Eatmentioning
confidence: 99%